ENGARUH KONSENTRASI MAMIGRO DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN KACANG ERCIS (Pisum sativum L.) - mufriah, dini; Lisdayani, Lisdayani; mayly, syarifa (Universitas Medan Area, 2025)
Efforts to increase the growth and yield of peas by providing foliar fertilizer or chicken manure. If the dose, type, time, and method of fertilization are correct, the plant's response to fertilizer application can increase growth and yield. This study aims to determine the effect of plant growth on the provision of Mamigro concentration and chicken manure on pea plants. This study used a Randomized Block Design consisting of two factors and repeated three times. Factor I is the concentration of Mamigro (M), consisting of 3 levels, namely M0 (Control), M1 (2 g / L), M2 (4 g / L). Factor II is chicken manure (P) consisting of 3 levels, namely, P0 (Control), P1 (1 kg / plot), P2 (2 kg / plot). The observation parameters are plant length, number of leaves, flowering days. The provision of Mamigro concentration has a significant effect on the parameter of flowering days. The best growth was found in the M2 treatment (Mamigro concentration 4 g / L). The provision of chicken manure has a significant effect on the parameters of plant length, number of leaves. The best growth was found in treatment P2 (chicken manure 20 tons/ha). The best combination was found in treatment M1P1 (Mamigro concentration 2 g/L and chicken manure 10 tons/ha)